The Effect of Work Commitment and Job Satisfaction on Employee Performance of PT Bank Mandiri Kcp Kadipaten, Majalengka Regency - Moh. Irfan Amirullah; Ade Sobariah Hasanah; Dini Tiara Tajriani; Rahmatika Siregar (Politeknik Mardira Indonesia, 2025)
This research aims to find out the impact of commitment to work and job satisfaction on the performance of employees of PT Bank Mandiri KCP Kadipaten either simultaneously or partially. In this study, the independent variables are job commitment (X1) and job satisfaction (X2) while the dependent variable is employee performance. (Y). The technique used in sampling is non-probability sampling. The data type used in this study is primary data. Data collection techniques using questionnaires. Data analysis techniques used in the study are classical assumption test analysis, double linear regression, and hypothesis test (t test and F test). The results of the research processed with the SPSS Version 21 for windows program showed that the R Square value of 0.886 means 88.6%, the staff performance variable can be explained by an independent variable in the study of job commitment and job satisfaction while the remaining 11.4% is explained with other variables that are not studied or not included in this regression model. Simultaneous test results (F Test) showed that the significance of 0.000<0.05, the commitment of work (X1) and the satisfaction of the job (X2) simultaneously had a positive and significant impact on the performance of employees (Y) in PT Bank Mandiri KCP Kadipaten. The partial test results (T Test) indicated that the meaning of the work commitment (X1) 0.041 < 0.05 tcount value of 0.329 > table 1.68288 means that the employment commitment has a positive impact on staff performance (Y), the value of employment satisfaction (X2), 0.000 < 0.05, the titing value of 0.723 > table 1.68288, meaning that job satisfaction has a significant positive effect on performance of staff (Y).